MANAGEMEN KOMUNIKASI PENGELOLA RUMAH SINGGAH DALAM PROSES PRA DAN MASA PEMBINAAN ANAK-ANAK JALANAN - Yayu Sriwartini; Dwi Kartikawati (Jurnal Ilmu dan Budaya, 2015)
This study was aimed to describe (1) how the House Shelter Managers of SEKAR do the communication and interaction process with the street children before coaching; (2) What kind of the roles of the House Shelter Managers of SEKAR in coaching the street children; (3) How the House Shelter Managers of SEKAR do the communication and interaction processin building familiarity with the street children assisted by themData collection techniquesused were(1) in-depth interview to the managers of the shelter SEKAR and street children, (2) as well as library research and documentation. The validity Test of the datas by either (a) went straight to the field, (b) used more than two informants to obtain precise data and notsubjective, (c) confirming the data on resources, (d) presenting the data in detail, systematically and Comprehensive, (e) discussing with colleagues. The results showed that the manager SEKAR always: (1) creating the warmth verbal communication by improving communication both to the street children themselves and the parents of these children, (2) improvingthe search through the introduction of information about the child and his approach to his parents, (3) creatingthe conducive conditions that emerge the children to reveal his true identity. Besides that, the role as brother, parents and friends raised by the managers as part of the management of symbolic communication to create a positive self-concept’s children. Then, in building interpersonal relationships with street children, there are two waysthat were: 1) expandinng the scope of activities. This is indicated in a variety of activities programmed by the manager of SEKAR. (2) deepening communication materials in a way to chat and give advice every bedtime, as well as being a friend to vent. The Conclusion of this research is that the communication management done by systematically starting from the contact, reduction of uncertainty. Additionally, the role of management is maximized to create interpersonal relationships and leads to a change in attitude and behavior of the street children normatively.